2008
DOI: 10.1002/jsfa.3325
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermentation metabolites on rheological and sensory properties of fermented rice noodles

Abstract: BACKGROUND: Considering the effect of natural fermentation on the textural improvement of fermented rice noodles in China and South Asia, and given the lack of reports concerning the roles of fermentation metabolites (enzymes, organic acids, glucose and maltose), this study aims to determine fermentation metabolites produced during fermentation of raw milled rice grains, and investigate their effects on rheological and sensory properties of rice noodles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…It indicates that protein and lipid contained in the flour blocked the reassociation of starch molecules during aging and, thus, delayed starch retrogradation. In a previous study, removal of all protein and lipid by means of trypsin, lipase, or physical extraction methods significantly improved the texture of rice noodles (Lu et al 2008). Baxter et al (2004) reported that addition of prolamin to rice starch causes an increase in RVA breakdown but decreases hardness, adhesiveness, and gumminess of the starch gel.…”
Section: Discussionmentioning
confidence: 98%
“…It indicates that protein and lipid contained in the flour blocked the reassociation of starch molecules during aging and, thus, delayed starch retrogradation. In a previous study, removal of all protein and lipid by means of trypsin, lipase, or physical extraction methods significantly improved the texture of rice noodles (Lu et al 2008). Baxter et al (2004) reported that addition of prolamin to rice starch causes an increase in RVA breakdown but decreases hardness, adhesiveness, and gumminess of the starch gel.…”
Section: Discussionmentioning
confidence: 98%
“…Meanwhile, the lactic acid produced by LAB could modify the characteristics and improve the sensory properties of rice noodles. [24] The potential to modify and purify the structure of rice starch by means of LAB is beneficial to rice noodle making. Therefore, further investigations about the enzyme activities and lactic acid production of the dominant LAB species could be performed in order to develop a rice noodles fermentation starter with better quality and stability.…”
Section: Analysis Of Lab Diversity Based On 16s Rrna Sequencesmentioning
confidence: 99%
“…Previous studies have reported that the decrease in protein content during rice fermentation correlated with development of the characteristic texture and transparency of Chinese fermented rice noodles (Lu et al ; Lu et al ; Lu et al ). Protein digestion liberates starch granules and removes granule‐associated proteins, which makes the starch gelatinize more readily during heating (Arai, Aoyama and Watanabe ).…”
Section: Introductionmentioning
confidence: 97%
“…In the previous study, the micro‐organism count peaked after 20–24 h of fermentation and then decreased (Siriroj et al ). Other studies found that lactic acid bacteria, such as Lactobacillus , Leuconostoc , Pediococcus , and Streptococcus species, were the major micro‐organisms found in fermented rice that is used to produce khanom ‐ jeen and Chinese fermented rice noodles (Toyoda et al ; Uchimura et al ; Lu et al ). These bacteria produce lactic acid, which acts as a preservative in fermented rice noodles.…”
Section: Introductionmentioning
confidence: 99%